Effect of Pellet and Mash Diets Associated with Biozyme Enzyme on Broilers Performance - Sarvestani, T. Shafiee; Dabiri, N.; Agah, M.J.; NoroIIahi, H. (International Journal of Poultry Science, 2006)
This experiment was conducted to investigate the effect of form of diets with different levels of biozyme enzyme on broilers performance. 800 Arbor Acres strain chickens were used in a factorial arrangement 2×3 with 2 form of diets (pellet and mash) and 3 levels of biozyme (0, 0.75 and 1.5 kg/ton) in a randomized completely design with 6 treatments and 3 replicates in each treatment and 45 birds/replicates. The weight gain (WG), feed intake (FI) and feed conversion ratio (FCR) were measured weekly from week 1-6. Carcass components were recorded at the end of trial (day 42). The WG were significantly (P< 0.05) greater in broiler fed pellet diets than comparable groups. The birds fed diet containing 0.75 kg/ton biozyme had greater WG (56.31 vs. 54.77 and 54.57 gram) and better FCR (1.7 vs. 1.79 and 1.84) than birds fed diets containing the two others levels. The weight of breast, thigh, abdominal fat and liver were significantly (P< 0.05) greater in broilers fed 0.75 kg/ton Biozyme and pellet diet. Heart weight in broilers fed pellet diets were significantly (P< 0.05) heavier than the broilers fed mash diets (9.56 vs. 8.056 gram). On, the other hand, Right ventricle to Total ventricle ratio was not affected by form of diet. It is concluded that the performance and carcass characteristics were improved in pellet diets.